Competencias Profesionales de los Docentes y su relación con la Calidad en la Educación Universitaria de los Estudiantes de la Facultad de Educación de la Universidad Nacional Federico Villarreal - Quiroz Florentini, Gabriel (2021)
The purpose of the work was to know the correlation between the Professional Competences of Teachers and Quality in University Education. The study methodology was the correlational, not experimental, the spatial field of study was the UNFV, the sample was 60 students from the tenth cycle of studies of the Faculty of Education, who were evaluated though two survey questionnaires, the first to evaluate the Professional Competencies of Teachers and the second to evaluate the Quality in University Education. The results found show that there is a positive, significant and medium-level relationship rho = 0,611 between Professional Teaching Competencies and Quality in University Education; Between Competencies in General Training and Quality in University Education the correlation was positive, significant and of a low level rho = 0,373, Likewise, between the Competences of Teachers in Pedagogical Training and Quality in University Education, the correlation was positive, significant and of  a medium  level rho = 0,566, also between Skills in Specialized Training and Quality in University Education, the correlation was positive, significant and of a low level rho = 0,270. The conclusions establish that there is a relationship between the mentioned variables. Keywords: Quality; work satisfaction; quality in education university; pedagogical training.